FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Nur Mufid (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2020)
This study aims to examine the relationship between debt to equity and systematic risk on stock returns of pharmaceutical companies listed on the Indonesian stock exchange. The object of this research is a pharmaceutical company listed on the Indonesia Stock Exchange (IDX) with the financial reporting period of 2014-2017. The sampling technique in this study was purposive sampling and obtained eight samples. The test method used in this research is multiple regression analysis method. The results showed that the debt ratio (DER) had no effect on stock returns, while the systematic risk (BETA) had a significant effect on stock returns. The implication of this research is that it provides an understanding for investors in making investment decisions to consider the fundamental analysis of financial information in estimating the stock returns that will be received. In addition, investors must also consider and pay attention to the risks that will be obtained which will certainly affect stock returns.